2018
DOI: 10.1007/s12630-018-1143-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hyperoxia on outcomes after cardiac surgery: a systematic review and narrative synthesis

Abstract: International Prospective Register of Systematic Reviews (PROSPERO) (CRD42017074712). Registered 17 August 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…1,2 Thus, the modulation of the biological process of CSCs is a reasonable therapy of heart failure. 5 Cai et al 6 found that modulation of hCSCs proliferation by CoPP resulted in greater improvement in left ventricular (LV) remodeling and cardiac function after infarction. 3 Wang et al 4 demonstrated that transplantation of Isl1 + cardiac progenitor cells (CPCs) seeded in small intestinal submucosa extracellular matrix (SIS-ECM) represents an effective approach for cell-based heart therapy.…”
mentioning
confidence: 99%
“…1,2 Thus, the modulation of the biological process of CSCs is a reasonable therapy of heart failure. 5 Cai et al 6 found that modulation of hCSCs proliferation by CoPP resulted in greater improvement in left ventricular (LV) remodeling and cardiac function after infarction. 3 Wang et al 4 demonstrated that transplantation of Isl1 + cardiac progenitor cells (CPCs) seeded in small intestinal submucosa extracellular matrix (SIS-ECM) represents an effective approach for cell-based heart therapy.…”
mentioning
confidence: 99%
“…2,3 Recently, Heinrichs et al synthesized these contemporary data in a systematic review as a means of understanding the level of evidence surrounding the use of various oxygen strategies in this setting. 4 Although the review generally concurs with the skepticism for the use of hyperoxia, as outlined by Guensch et al, the reasons for doing so incorporate other features as to why such uncertainty is warranted. The lack of consensus surrounding a universal definition of "hyperoxia" makes it particularly difficult to study the effect of this arguably unphysiologic intervention.…”
Section: Conflicts Of Interestsmentioning
confidence: 82%
“…Indeed, there may be times during cardiac surgery in which increasing oxygen levels greater than physiologic limits may be advantageous to reduce tissue hypoxia that can occur during cardiopulmonary bypass. 4,5 By reducing this ischemia with enhanced oxygenation, the subsequent reperfusion injury also might be reduced. Of cause for further concern is that the 2 largest studies to date, by Smit et al 2 and McGuinness et al 3 and curiously omitted in the editorial by Guensche et al, find no adverse effect of hyperoxia on either acute kidney or myocardial injury in cardiac care.…”
Section: Conflicts Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased oxygen concentrations are commonly administered during CPB in order to avoid cellular hypoxia, reduce gaseous micro-embolism, and improve neutrophils' functionality [71] . Nonetheless, enhanced production of ROS, cardiovascular dysregulation, and increased injury due to ischemia-reperfusion are some of the systemic effects linked to hyperoxia [72,73] .…”
Section: Hyperoxiamentioning
confidence: 99%